Fundamentals of Historical Materialism - Khatri, Tilak Bahadur (Cognition, 2023)
This article explores the basic tenets of historical materialism. It is relevant to identifying the general trends of historical materialistic critique of the evolution of human society. The article addresses the research problems concerning the conception of history, the relationship between base and superstructure, the significance of the mode of production, and the class struggle in the development of human history. The article deals with the problems through the review-based analysis of the historical materialistic critique of the rise of human society. The article reveals that the materialist interpretation of history is the key to historical materialism. The materialist conception of history interprets the basis of every social order according to production and the relation of production. It regards class struggle as the reflection of the conflict between the forces of production and the relation of production. The materialist conception of history views the mode of production or the economic base as the determining element in history but in many cases, the different forms of superstructure also react upon the base and play their role in changing the course of history.